Utilization of household waste through maggot cultivation in Lecari Village, Pasuruan Regency - Abdul Wahid; Sinta Nur Fadhilah; Nahdiyatus Syariva; Fikri Nur Syarifudin; Syamsyul Arifin; Marisannah Millatul Haq; Alifia Diana (Universitas Muhammadiyah Magelang, 2022)
This community service aims to make people care about household waste, turn waste into economic value, and have an impact on improving welfare after the pandemic. The program was carried out through an organic waste management workshop using black soldier fly (BSF) larvae media for residents of Lecari Village, Sukorejo District, Pasuruan Regency. The program was attended by 11 people where 3 of them were very interested in cultivating maggot and 6 people wanted to do trials. While the other 2 people are not interested in maggot cultivation. The results of this program will also be realized by the Village-Owned Enterprises (BUMDes) as an economic potential in order to improve the welfare of the Lecari Village community.